PERBEDAAN KADAR GLUKOSA DARAH PUASA PASIEN DIABETES MELITUS TIPE 2 PADA PLASMA NaF BERDASARKAN WAKTU PEMERIKSAAN DI RSUD dr. M. YUNUS PROVINSI BENGKULU TAHUN 2017 - Susiwati, Susiwati (Journal of Nursing and Public Health, 2018)
Blood glucose examination is needed as a diagnosis of Diabetes Mellitus disease. In a state of fasting no food is absorbed. The delay of examination causes glucose to be degraded and the value obtained is less than the value it should be. Anticoagulant NaF is used for the examination of blood glucose, because florida as antiglycolysis inhibits phosphoenol enzyme pyruvate and urease enzymes so that blood sugar levels are expected to be stable. This study aims to determine the difference of fasting blood glucose level of DMT2 patients in NaF plasma based on the examination time that is immediately checked and delayed 2 hours. It is pre experimental one group pretest-posttest design. Respondents were 30 patients with DMT2. Glucose levels were measured using NaF plasma which was promptly checked and delayed for 2 hours. The results of blood sugar levels immediately checked had an average value of 219.20 mg / dL and the average value of glucose with a delay of 2 hours was 210.67 mg / dL. The average difference of both is 8.53 mg / dL. The results of t test dependent show p <0.05 means there is a difference. Conclusion of this study there is a difference between fasting blood glucose levels in patients with DMT2 using plasma NaF based on inspection time. Glucose screening checks should be done directly without delay in order to obtain accurate examination results.